Development of Branding Innovation Strategies for RPD. Design Studio - Priambodo, Rezandra; Larso, Dwi (The Indonesian Journal of Business Administration, 2015)
Abstract - Creative industry is a sector that provides new opportunities in doing business, and it will always expand over time due to human creative ideas that never runs out. Indonesia with a population reaching 250 million people exposes the phenomenon whereby they need spaces to live, spaces for expression, space to work and much more. This is a great positive opportunity for design company players.RPD. Design Studio is a new design company that specializes in architectural and interior design service. Almost two years of operation, RPD. Design Studio runs its business with completing architectural and interior individual projects. Accordingly, RPD offers new service concepts of architectural design, interior design, graphic design, and photoproduct within one management company. One of the company problem recently is to be recognized widely especially in Bandung, not only by family members and friends.Strategic brand innovation management is used to be proper tool for company branding target. By scanning internal analysis like determining who the company prospect clients are and what is the basic concept of the company and scanning external analysis like competitors as a reference and how the right company branding strategy, then produced a perfect solution for company development.Based on the result of the companyâ€™s business plan analysis, the proposed innovation branding strategy is divided into several stages, which are completing Sukahaji project quick and precise; fixing design service standard procedure for internal company and for clients; supplementing the needs of organization structure by selecting the right people and doing promotion in cyberspace (social media) and a real built-in project promotion.Keywords: brand innovation management, architecture, interior, graphic design and photo products, and design studio.Â